"Building Spiritual Immunity": The Strategic Use of the Health Message in the Seventh-Day Adventist Church Media during the COVID-19 Pandemic - Kołodziejska, Marta (Nordic journal of religion and society, 2022)
The article investigates to what extent the Covid-19 pandemic has influenced the Seventh-Day Adventist Church’ health message. Based on the results of the study of media content and interviews with Adventist media producers in Poland and the UK conducted in the spring of 2020, this article argues that the pandemic has led to an intensification of health-related productions within the SDA Church in Poland and the UK, and a growing media awareness (in terms of when, how, and what to publish). As a result, a transformation of the communicative figuration can be observed, pertaining primarily to the communicative practices of actors and to the actors’ constellation.